THE EFFECT OF COURSE REVIEW HORAY MODEL ON STUDENTS’ WRITING DESCRIPTIVE TEXT ABITITY (A study at the Eighth Grade of SMP Negeri 4 Sorkam in 2020/2021 Academic Year) - Hotnauli Nurcahaya Situmeang (JURNAL LINER (Language Intelligence and Educational Research), 2021)
ABSTRACT Situmeang, Hotnauli Nurcahaya. 2020. The Effect of Course Review Horay Model on Students’ Writing Descriptive Text Ability (A study at the Eighth Grade of SMP Negeri 4 Sorkam in 2020/2021 Academic Year). Skripsi. Program Studi Pendidikan Bahasa Inggris. Institut Pendidikan Tapanuli Selatan. The purpose of this research are to found out: 1) The application of course review horay model on students’ writing descriptive text, 2) The students’ writing descriptive text ability before and after using course review horay model, 3) whether there is any significant effect of course review horay model on students’ writing descriptive text ability at the eighth grade of SMP Negeri 4 Sorkam. This research used an experimental method. The population of this research is all the eighth grade students which consist of 102 students and the samples were 22 students gotten by using purposive sampling. In collecting the data, the researcher used an observation sheet. The instrument of the research was observation and the test was a composition test. The result of the research are 1) application of course review horay model was 3.8, it was categorized “very good”. 2) The mean score of the students’ before using course review horay model was 53, it was categorized “bad”. Meanwhile after using course review horay model was 73, it was categorized “good”. 3) The result of the analysis showed that the t-test is bigger than t-table (ttest12.82> t-table 2.08). So, the hypothesis was accepted. It means that there is any significant effect of course review horay model on students’ writing descriptive text ability at the eighth grade of SMP Negeri 4 Sorkam. Keyword: Course Review Horay, Model, Writing, Descriptive Text